The information technology era of the vehicular industry. - Ernst, Thierry (Computer communication review.)
In this note, we discuss the emerging era of information technology in the vehicular industry. After reviewing the motivations leading to the use of information technology in vehicles, we investigate the networking requirements of the necessary communication system based on IP (Internet Protocol). Existing work that could meet these requirements is highlighted together with some existing projects. We also briefly introduce some research and deployment issues that will have to be considered.